The Systems Thinking Playbook for Climate Change - Booth Sweeney, Linda (2011)
Simple interactive exercises, we call them ‘games’ or ‘strategic exercises’, have the potential to help participants understand by doing. In The Systems Thinking Playbook for Climate Change, we present 22 games that will be useful to those who are trying to communicate with others about the causes and consequences of climate change. These simple exercises can facilitate the process of communication and education.